Paradigma Sufistik Dalam Kitab Rasail al-Junaid Karya Imam Junaid al-Baghdadi - Siti Rahma; Ade Nur Rahmadhani; Saifullah (Mazalat: Jurnal Pemikiran Islam, 2026)
Sufism is an important pillar in Islam that emphasizes self-purification and a spiritual approach to God. This study examines Imam Junaid Al-Baghdadi's Sufism concept through the book Rasail al-Junaid using qualitative methods of literature study and content analysis. The main focus of the study is to explore Imam Junaid's Sufism teachings that emphasize monotheism, mitsaq, fana, sahw, zuhud, dhikr, wara', and their application in modern life. The results of the study show that Imam Junaid's Sufism is not only oriented towards spiritual experience, but also prioritizes harmony with the Shari'a and the development of noble morals. Concepts such as fana-baqqa emphasize the importance of eliminating the ego and maintaining awareness of God's presence. The implementation of these teachings is relevant to addressing the spiritual and moral crisis of modern society trapped in materialism and identity crises. By cleansing the heart, increasing spiritual awareness, practicing noble morals, and implementing the qualities of patience, gratitude, and contentment, Imam Junaid's Sufism provides a holistic solution to the challenges of the times. In conclusion, Imam Junaid al-Baghdadi's understanding and practice of Sufism offer a strong ethical and spiritual foundation for strengthening faith and spiritual balance in the contemporary era.